Analisis Pandangan Masyarakat Terhadap Perbankan Syariah - Rizqiyah, Anisah; Maysarah, Maysarah; Vanessa, Vanessa; Anggraini, Tuti (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
Payageli village hamlet 1 is a village in Deli Serdang with a majority Muslim community. However, most Muslims in this village still do not understand sharia-based banks. Sharia banks are commercial institutions whose function is to collect public money and distribute money to the public with commercial operational systems and mechanisms based on Islamic law specified in the Al-Quran and Hadith. This research aims to provide information regarding the views of the village community regarding sharia banking. This research uses a qualitative method using a descriptive approach. Data collection in this research used observation, interviews, documentation and questionnaires. The conclusion of this research shows that the Payageli village community is aware of the existence of sharia banks. However, the people in this village still lack knowledge about the products and services available at sharia banks and there is a lack of education about sharia banking so that the people in this village are comfortable with conventional banks.